PHYSICAL DISTANCING PERSPEKTIF MAQASHID AL-SYARI’AH STUDI DI DESA LAMENDORA KECAMATAN KAPOIALA KABUPATEN KONAWE - Nurrahman, Panji (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
This study aims to determine the concept of psychological distancing and the impact of its application on people's lives, as well as to find out how the maqa>s}id al-Shari'ah review of physical distancing. To answer this problem, this research uses a type of field research, with data collection methods, namely observation, interviews, and documentation. Sources of data in this study are primary data and secondary data. Primary data in this study was obtained from interviews with people who directly felt the impact of physical distancing in Lamendora Village, while secondary data was obtained from documents in the form of books, scientific research articles, and from the internet that are related to this research. The results of this study conclude three main points. First, physical distancing is an effort to inhibit the spread of the COVID-19 virus by maintaining physical distance and not creating crowds. Second, the implementation of physical distancing has an impact on economic life, education, religion, as well as on family. Third, based on the analysis of maqa>s}id al-Shari'ah that during the COVID-19 pandemic the law is mandatory for the sake of realizing the benefit of humans. In addition, the application of physical distancing includes efforts to maintain maqa>s}id at the d}aruriya>t level which includes: maintaining the soul, maintaining the mind, maintaining property, maintaining offspring and maintaining religion.